Comparison of DAF Pretreatment between Static Mixer and Impeller Mixer for Oil and Grease Reduction - Novembrianto , Rizka; Rosariawari, Firra; Cahyonugroho, Okik Hendriyanto; Nisa', Syadzadhiya Qothrunada Zakiyayasin; Sitogasa, Praditya Sigit Ardisty; Murti, Restu Hikmah Ayu (Future Science, 2023)
The problem of domestic wastewater originating from restaurants is the largest contributor to organic wastewater in urban waters. Among them are waste water parameters, namely oil, and grease. Oils and grease are compounds that do not dissolve easily in water. However, it can be dissolved with non-polar organic solvents. The carbon chains of oils and grease are also long. So, it is difficult to decompose and takes a long time if processing uses the help of microorganisms. So, the alternative is to use physical-chemical processing. In this research, we tried using a static mixer and an impeller mixer. We conducted a systematic review of DAF techniques in wastewater treatment. We reviewed six indexed databases namely dissolved air flotation, microbubbles, wastewater treatment, and key operational and design parameters involved in the effectiveness of the flotation process. In this pre-treatment, the focus is on the withdrawal/discharge speed in collecting wastewater as a test and the effectiveness of mixing wastewater with coagulants and air pressure. These three aspects are used in equilibrium to achieve the optimum dose for the static mixer use scheme. Meanwhile, the impeller mixer scheme uses rotational speed in mixing with the coagulant, contact time, and Reynolds number to achieve the required turbulence. Apart from that, the use of electrical energy in the pump is also calculated in these two schemes. The results obtained were the amount of weight of oil and grease collected in the static mixer pretreatment of 9.12% w/v and the impeller mixer of 7.63% w/v and the results of the organic content of the Chemical Oxygen Demand (COD) parameter for the static mixer were 86.92 % and mixer impeller 78.86 %. From these results, static mixers have advantages over using impeller mixers in terms of the effectiveness of the oil and grease reduction process.